Pemberdayaan Perempuan dalam Pengelolaan UMKM: Studi Kasus Usaha Kelompok Mandiri Weluwini di Desa Manulondo, Kecamatan Ndona, Kabupaten Ende (Lembaga Pengembangan Kinerja Dosen, 2025)
Empowering women in rural areas is one of the strategic approaches in supporting local economic development and poverty alleviation. Empowering Women in Managing MSMEs in Mandiri Weluwini Group Businesses in Manulondo Village, Ndona District, there are obstacles in terms of business management. This research is a qualitative descriptive study. The data collection techniques for this study are interviews, observations and various documents. Then analyzed using qualitative analysis with comparative techniques. The results of this study indicate that empowerment can be seen from 4 indicators, the first Access to Resources where women working in Weluwini MSMEs have relatively open access to economic resources, knowledge resources, most of their skills are obtained, namely through direct work experience in the field. The second Participation, where the involvement of women in the operations of Weluwini MSMEs is fairly active. However, in the process of making strategic or internal business decisions, such as determining salaries, financial management, and the direction of business development, female employees are not always involved. The third Control, In terms of control, it was found that women have an active role in monitoring the quality and efficiency of work. some employees even feel the need to remind fellow co-workers if there is negligence or a decline in quality. And the fourth benefit, the empowerment that occurred in Weluwini UMKM has provided significant benefits, both economically and socially.